An Inventory of Nutrient-Responsive Genes in Arabidopsis Root Hairs - Salazar-Henao, Jorge E.; Schmidt, Wolfgang (Frontiers in Plant Science, 2016)
Root hairs, single cell extensions of root epidermal cells that are critically involved in the acquisition of mineral nutrients, have proven to be an excellent model system for studying plant cell growth. More recently, omics-based systems biology approaches have extended the model function of root hairs towards functional genomic studies. While such studies are extremely useful to decipher the complex mechanisms underlying root hair morphogenesis, their importance for the performance and fitness of the plant puts root hairs in the spotlight of research aimed at elucidating aspects with more practical implications. Here, we mined transcriptomic and proteomic surveys to catalog genes that are preferentially expressed in root hairs and responsive to nutritional signals. We refer to this group of genes as the root hair trophomorphome. Our analysis shows that the activity of genes within the trophomorphome is regulated at both the transcriptional and post-transcriptional level with the mode of regulation being related to the function of the gene product. A core set of proteins functioning in cell wall modification and protein transport was defined as the backbone of the trophomorphome. In addition, our study shows that homeostasis of reactive oxygen species and redox regulation plays a key role in root hair trophomorphogenesis.